PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN PADA MING COFFEE AND EATERY DI DENPASAR - Sudana, I Gede; Dwijayanthi, Anak Agung Istri Agung Ovy (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
The advantage of a company in winning the competition lies in customer satisfaction. Even in the midst of increasingly fierce business competition, the companies that are run are still able to survive and excel because customers feel they are getting the service they want. The formulation of the problem in this study is: Does service quality partially effect customer satisfaction at Ming Coffee and Eatery in Denpasar? Does customer value partially effect customer satisfaction at Ming Coffee and Eatery in Denpasar? Does service quality and customer value simultaneously effect customer satisfaction at Ming Coffee and Eatery in Denpasar? The research objective was to analyze the effect of service quality partially on customer satisfaction at Ming Coffee and Eatery in Denpasar. To analyze the influence of customer value partially on customer satisfaction at Ming Coffee and Eatery in Denpasar. To analyze the effect of service quality and customer value simultaneously on customer satisfaction at Ming Coffee and Eatery in Denpasar. The number of samples was determined as many as 96 customer respondents at Ming Coffee and Eatery in Denpasar. Data were analyzed using multiple linear regression analysis. The results showed that service quality had a positive and significant effect on customer satisfaction at Ming Coffee and Eatery. Customer value has a positive and significant effect on customer satisfaction at Ming Coffee and Eatery. Service quality and customer value have a positive and significant effect on customer satisfaction at Ming Coffee and Eatery.